RISK ASSESSMENT OF RATTAN MANUFACTURER AS BUSINESS IMPROVEMENT (CASE STUDY: CV. TROPICA RATTAN) - Pratama, Reyhan; Rahadi, Raden Aswin (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
Indonesia's rattan industry, a major contributor to the Indonesian economy, faces significant challenges, such as fluctuating raw material supply, rising production costs, and competition from synthetic furniture products. CV Tropica Rattan, a mid-sized company in Cirebon, faces the challenges of declining export performance and limited innovation. This study applies a customized risk management framework to address operational and financial risks that may affect CV Tropica Rattan. Internal and external analysis was conducted using Business Model Canvas and PESTLE to identify possible risk factors. The Analytical Hierarchy Process was then used to prioritize the risks to implement mitigation strategies efficiently. Semi-structured interviews and focus group discussions provided qualitative insights, while secondary data was used to support contextual analysis. The results show that structured risk management can improve the company's resilience and competitiveness while providing a model that can be used for similar MSMEs in the rattan industry. This research contributes to understanding how tailored risk strategies can promote sustainable growth and operational efficiency in traditional manufacturing.